Upaya Meningkatkan Hasil Belajar IPA Siswa Kelas V SDN 104252 Sei Tuan Dengan Menggunakan Media Komputer Pada Materi Benda dan Wujudnya - Nuri Ramadhan; Maringan Sihombing (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This type of research is classroom action research, which consists of 4 stages, namely planning, implementing, observing and reflecting. Based on the results of the study it can be concluded that of the 20 students only 5 students (25%) have completed the writing skills of Indonesian language lessons, and 15 students are still not finished. Based on the results of the initial test, the researcher took action using the Picture and Picture learning model in the first cycle of the first meeting, the results obtained by student observations were (48.35%) at the second meeting of the first cycle, the results obtained were student observations (50.23%) These observations obtained an average value of (49.29) and classified as Low. In addition to student observations, teacher observations were also carried out in cycle I and obtained a value of (61.11%) at the first meeting, (76.38%) at the second meeting, from the results of teacher observations obtained an average observation of (68.74%) %) and is quite good. Based on the data from cycle I, the value is still not good, so the researcher continues the action in cycle II. At the first meeting in the second cycle the results of student observations were (80.15%) and at the second meeting the results of student observations were (80.65%), from the two observations, the average result of student observations was (80, 4%). And classified as complete. The results of teacher observations in the second cycle of the first meeting obtained (84.72%) and (88.88%) results at the second meeting of the data obtained that the average value of teacher observations was (86.8%) and classified as high. After the end of the actions in cycle I and cycle II, the researcher again gave Writing Skills Tests to the students and the results were that from 20 students 16 students (80%) were included in the improved and complete category, while 4 students (20%) were still classified as in the incomplete and non-increasing category.